SYSTEMATIC REVIEW: THE EFFECT OF ADOLESCENT BEHAVIOR ON UNWANTED PREGNANCY - Ach. Fahrizal Amien (Indonesian Midwifery and Health Sciences Journal, 2023)
One indicator of the country's progress can be seen from the maternal mortality rate in which adolescents are the group of contributors to this figure. Pregnancy is unwanted to be the cause of maternal death because of the many complications during pregnancy and childbirth. Not to mention the other postpartum impacts that must be borne by adolescents. Many factors influence unwanted pregnancy, one of which is the factor of adolescent behavior itself, of course, there are many factors that influence adolescent behavior, which causes unwanted pregnancy. The aim of this study is to see what aspects of adolescent behavior affect unwanted pregnancies This study is a literature study of several journals, theses, and other scientific articles on behaviors that affect unwanted pregnancy in adolescents. Adolescent behavior factors for unwanted pregnancy include beliefs & perceptions about premarital sexual behavior and contraception. From a cognitive point of view where the level of knowledge related to pregnancy is undesirable. A negative attitude will encourage adolescents to engage in risky behavior. Adolescent motivation which becomes the reason for engaging in risky behavior is the need to fulfill adolescent lifestyles. The risky actions that affect unwanted pregnancies are the behavior of consuming alcohol, illegal drugs, and not using contraceptives.